Assessment of Single European Sky Implementation in the Functional Airspace Block Central Europe - Mihetec, Tomislav; Vidović, Andrija; Rezo, Zvonimir (Promet - Traffic&Transportation, 2017)
Implementation of Air Traffic Management (ATM) Master Plan-defined projects represents a prerequisite for the successful implementation of the Single European Sky initiative defined by the European Commission in 2004. The implementation of ATM-related projects is currently under the responsibility of the Single European Sky Research Programme Deployment Manager. While the definition of projects is being performed at the European Network level, the implementation is performed through sub-regional grouping of Air Navigation Service Providers in a form of Functional Airspace Blocks. This paper analyses the level of implementation of ATM-related projects in the Functional Airspace Block Central Europe and their relation to other Functional Airspace Blocks defined in Europe. From this paper it is obvious that even though the planning of Single European Sky projects is based on the collaborative implementation of Functional Airspace Block level, the real implementation is fragmented and based on national levels.